(untitled) (Global Journal of Science Frontier Research, 2022)
The aim of this research to investigated physical and mechanical properties of thermal plywood of PF adhesive Physical property focused on density water absorption and swelling And mechanical property was MOR MOE shearing strength and hardness The Teak veneer was the main raw material the size was 2 mm in thickness and 400 mm in width and length The veneer was divided into five groups as were control thermos-veneer at 180 C at 200 C 220 C and 240 C and 4 min 8 min and 12 min the spread 150 g m2 and five layers Plywood products used PF adhesive products were cool pressing in 10 min and hot pressing in 15 min density test followed with AS ANZ 2098 7 2012 WA and swelling thickness were followed ASTM D 3502-76 The dimension sample design was 10x25x300 mm for MOR and MOE 10x50x100 mm for shearing strength and 10x50x50 for harness and testing by Fast Test software Data analyses were One-way ANOVA and multiple linear regression As the result the density of thermal treatment was decreased density of teak plywood A control was significant different on thermal treatment of different level of temperature and length of time the control was no significant different WA in the different level of temperature and length of time the WA increases The control was significant different with thermally Swelling thickness of thermal treatment at 180 220 240 C was increased to significant different with control and length of time the control was no significant different The MOR in different level of temperature the control was only significant with at 180 C and but another group at 200 220 and 240 C was no significant The length of time on 4 8 and 12 min was no significant different MOE was decreased in different level of temperature at 180 200 220 and 240 C significant different and length of time on 4 8 and 12 min was no significant different The different level of temperature effected MOE of teak plywood The shearing strength in different level of temperature at 180 200 220 and 240 C and length of time on 4 8 and 12 min were no significant different And the hardness in thermal treatment at 180 200 220 and 240 C and length of time on 4 8 and 12 min was fluctuated And it was no significant different